Dynamics of the Obligation to Register Birth Certificates as a part of the Right to Issuance Population Documents - Wijayanti, Winda (Constitutional Review, 2016)
The state is obliged to protect and recognise the legality of a personâs birth. Registration of birth in the form of a birth certificate is proof of oneâs origin issued by the competent authorities. However, in practice, the time limit of one year given for such registration has proven a burden to citizens, such that complaint of constitutional damages has been brought before the Constitutional Court of Indonesia. Population administration is regulated under Act Number 23, Number 23 Year 2006 and amended by Act Number 24, Number 24 Year 2013 in accordance with Constitutional Court Decision 18/PUU-XI/2013. In order to take an active role in the registration of births, the government and local governments have to remove the deadline to report the birth of a child, as stipulated by the district court and as an effort to improve state responsibility. This requires that citizens have the "right to be heard" and, in future, there should be an integrated service from the government for the registration of births.